2005
DOI: 10.1111/j.1439-0507.2005.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

The serum levels of calcium, magnesium, iron and zinc in patients with recurrent vulvovaginal candidosis during attack, remission and in healthy controls

Abstract: The real cause of recurrent vulvovaginal candidosis (RVVC) is concealed and the etiopathogenesis of this disease remains to be determined. In a cohort study, concentrations of metals in 44 patients with RVVC and 30 healthy age-matched women were measured and compared. The concentrations of serum calcium (Ca), magnesium (Mg) and iron (Fe) were measured photometrically, the zinc (Zn) levels were determined using flame atomic absorption spectrometry. For statistical analysis were used the Student's t-tests (paire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…Recent studies of the role of iron in recurrent vulvovaginal candidosis have revealed that this element is important not only for the normal function of host immunity but also for pathogenic Candida owing to the fact that absence of this metal resulted in reduced virulence and hence reduced yeast invasion of the host epithelium (40). Availability of iron has been found to play a critical role in different clinical infections, and this represents a challenge to investigate the role of iron more closely (5).…”
mentioning
confidence: 99%
“…Recent studies of the role of iron in recurrent vulvovaginal candidosis have revealed that this element is important not only for the normal function of host immunity but also for pathogenic Candida owing to the fact that absence of this metal resulted in reduced virulence and hence reduced yeast invasion of the host epithelium (40). Availability of iron has been found to play a critical role in different clinical infections, and this represents a challenge to investigate the role of iron more closely (5).…”
mentioning
confidence: 99%
“…However other studies did not find evidence to support the role of sugar consumption in genital candidiasis [78]. While deficiencies of minerals such as magnesium, zinc, calcium and iron have been associated with genital candidiasis in some studies, the evidence thereto is considered insufficient [79].…”
Section: Dietary Factorsmentioning
confidence: 85%
“…acute VVC, in a minority (< 10% of those who suffer one episode) it is recurrent, i.e. they experience at least 4 symptomatic episodes in a year [3,79,122].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased bone marrow iron stores is an independent risk factor for invasive aspergillosis in patients with haematologic malignancies [143]. Excess iron increases the virulence and invasive potential of yeast in recurrent vulvovaginal candidosis [144], and iron depletion increases the susceptibility of Candida to antifungal drugs [145].…”
mentioning
confidence: 99%